Femoral Nerve Block Intervention in Neck of Femur Fracture (FINOF): a randomized controlled trial - Rowlands, Martin; Walt, Gerrie van de; Bradley, Jim; Mannings, Alexa; Armstrong, Sarah; Bedforth, Nigel M.; Moppett, Iain K.; Sahota, Opinder (BMJ Publishing Group Ltd, 2018)
Objective